Competitive intelligence: Leaven of a New Managerial Device for Decision Support - Salima El Fadili; Firdaous Gmira (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In a highly competitive environment saturated in information traversing the earth in nanosecond, the major challenge for companies is to have the right information at the right time, to exploit it and transform it into useful organizational knowledge for strategy formulation and decision-making. Nowadays, several management practices have been developed and designed to cope with the complexity that exists in the business environment and to maintain a sustained competitive advantage. Competitive intelligence is one of these innovative strategic management practices that play an increasingly important role in decision-making. This article attempts to present an overview of its fundamental concepts, functions and process and to explain how information is utilized in supporting decision-making process. The findings of this research suggest that decision makers should focus on developing competitive intelligence process in their organizations. This paper falls under a research task that was not confronted yet with the test of the terrain survey.